Effects of Dissipative Systems on the Seismic Behavior of Irregular Buildings—Two Case Studies - Marco Miani; Caterina Di Marco; Giada Frappa; Margherita Pauletta (Buildings, 2020)
Conservation of heritage buildings has become a very important issue in many countries, as it is in Italy, where a great number of existing buildings of historical–artistic importance are seismically vulnerable. To improve existing building behavior, researchers focus on the design of retrofit interventions. This paper presents the application of energy dissipation devices in the retrofit of two existing Reinforced Concrete (RC) buildings, both irregular in plan and along their heights, designed for gravitational loads only. These buildings are representative of Italian public housing built in the 1960s and early 1970s. Technical information and mechanical properties of materials are presented, and non-linear analyses are carried out to evaluate the buildings’ behavior under earthquake loads. Many of their structural members do not satisfy the verifications required by the Italian Building Code. Retrofit interventions with buckling-restrained axial dampers in one building and viscous fluid dampers in the other are proposed. The verifications of the retrofitted buildings and the amount of the energy absorbed by the devices with respect to that absorbed by the unretrofitted buildings show the effectiveness of the proposed interventions. Moreover, it is demonstrated that adequate dispositions of the dissipative devices in plan and along the height increase the torsional stiffness of the buildings, improving their structural response under seismic action.